A novel type of cosavirus from children with nonpolio acute flaccid paralysis. Issue 1 (December 2016) - Yang, Yan; Ju, Aiping; Xu, Xiaofen; Cao, Xinyu; Tao, Ying
Abstract Human cosavirus (HCoSV) is a genus recently identified in the family Picornaviridae, which contains important pathogens to human health. Here, a novel type of HCoSV strain, cosavirus-zj-1 (GenBank no. KX545380), was identified in the fecal sample of a child with nonpolio acute flaccid paralysis (AFP) in China. Phylogenetic and sequence analyses suggested that this virus strain belonged to a new genotype in HCoSV B species. Our data show that surveillance of HCoSV is necessary for detecting viral agents in children with AFP, despite being the low detection rate.